A Geographical Appraisal of The Expansion and Deterioration of The Indian desert - Sen, Amal Kumar; Mann, H S (Annals of Arid Zone, 2016)
An attempt has been made in the paper to examine the creep and deterioration of Indian desert on the basis of some physiographic and topographic parameters. The extent of the Great Indian Desert and its geographic limits have been defined. The Indian desert has been identified as a true desert. The creep of the desert has then been considered in relation to the increase and decrease of desertic sand-the extent of sand dunes-water table and climatic phenomenon-drainage system and soil. The paper includes a note on the causes of the deterioration of the conditions within the desert.